Fuzzy Cognitive Map of Vulnerability by Interactive Qualitative Analysis - Tseng, Ching-Chuan (Archives of Business Research, 2019)
Along with the internationalization and globalization, the rapid change of the era, and the increase in the diversification of customer demands, business management is facing intensive turbulence. Currently, the financial industry in Taiwan is at the era of radical changes in the external environment and fast revolution in information technology. It forces the operators in the financial industry to equip themselves with certain knowledge and responding capability for the business risk at the external environment in order to be ready to provide a situation-conforming and concrete revolutionary proposal for the financial crisis encountered. The article uses business risk in the financial institutions as the research topic and constructs fuzzy cognitive maps based on the perspective of vulnerability and resilience. The research outcome reveals the factors that affecting vulnerability including risk appetite, compliance, operational management, organizational culture, and internal audit as well as the frequency of communication & negotiation and external linkage.